1997
DOI: 10.1021/ja971829p
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Cyclopentadienylnickel Methoxo and Amido Complexes:  Synthesis, Characterization, Reactivity, and Use for Exploring the Relationship between H−X and M−X Bond Energies

Abstract: Reactive monomeric amido and methoxo complexes, Cp*Ni(PEt3)NHTol and Cp*Ni(PEt3)OMe, have been synthesized and fully characterized. The former is the first monomeric 18-electron nickel amide to be synthesized and the latter is the first structurally characterized monomeric nickel methoxide complex. The amido complex Cp*Ni(PEt3)NHTol reacts with various Brønsted acids (HX) to produce complexes of the type Cp*Ni(PEt3)X (X = NHAr, OR, Osilica, SR), and compounds with hydridic hydrogens to give the hydridonickel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
127
0
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(139 citation statements)
references
References 110 publications
11
127
0
1
Order By: Relevance
“…It has often been asserted that late metal-oxygen and -nitrogen bonds are weaker than their early-metal counterparts, but if we focus on specific homolytic bond dissociation energies (BDEs), rather than average bond energies, only a few studies have been carried out to test this expectation. 29,30 More systematic information is available about relative (rather than absolute) bond energies. In a widely cited study by Bryndza, Bercaw, and co-workers, a correlation was proposed between the relative bond strengths of metal-heteroatom bonds (M-X) and their corresponding acids (H-X).…”
Section: Direct Studies Of the Primary Reactions Of Metal Alkoxides Amentioning
confidence: 99%
“…It has often been asserted that late metal-oxygen and -nitrogen bonds are weaker than their early-metal counterparts, but if we focus on specific homolytic bond dissociation energies (BDEs), rather than average bond energies, only a few studies have been carried out to test this expectation. 29,30 More systematic information is available about relative (rather than absolute) bond energies. In a widely cited study by Bryndza, Bercaw, and co-workers, a correlation was proposed between the relative bond strengths of metal-heteroatom bonds (M-X) and their corresponding acids (H-X).…”
Section: Direct Studies Of the Primary Reactions Of Metal Alkoxides Amentioning
confidence: 99%
“…49 Previous experimental studies have revealed that M-OR BDEs can be greater than M-C BDEs. 40,[81][82][83][84][85][86] (PH 3 ) 2 OH is 74 kcal/mol at the same level of theory. Thus, oxidation from Ru(II) to Ru(III) is calculated to decrease the Ru-X hydroxyl BDE by only 32%, a value that is proportionately less than the impact of single-electron oxidation on Ru-alkyl BDEs.…”
Section: Resultsmentioning
confidence: 92%
“…These reactions are two of few known examples of such reactions. To our knowl- edge, the only other reported transition-metal amide reaction to give an isolated amide hydride involves Cp*Ni(PEt 3 )NHTol [12].…”
Section: Reactions Of D 0 Amide Complexes M(nme 2 ) 4 (M=ti Zr Hf) mentioning
confidence: 95%